Managing Income Creatively by Young Entrepreneurs in Bandung - Elizabeth Tiur Manurung; Elvy Maria Manurung (International Review of Management and Marketing, 2019)
Business competition is getting fiercer nowadays, especially in the city of Bandung, area of West Java in Indonesia. Moreover, today's consumers are increasingly savvy and choosy. The presence of several new cafés and restaurants for the past five years in this city indicates that not only food and beverages are served, but that facilities for hanging out, playing and studying are being provided as well. This phenomenon has made an impact on young entrepreneurs in Bandung to further explore their creativity, as an unavoidable reality. A great deal of research has been conducted to examine the presence of cafés and restaurants affecting the lifestyle of users, but not many studies have focused on the creativity of the owners (entrepreneurs) in managing their income. This research has been conducted using qualitative methods, namely observation and interviews in order to reveal how the situation of market competition affects the creativity of these young entrepreneurs in managing their businesses, especially their income. Seven cafés and restaurants were selected through popularity criteria in initial discussions with students and ratings from websites, to become objects of observation. One hundred thirty-three respondents were randomly selected and interviewed when they visited the object under study. The results of the study show that young entrepreneurs have unique ways of attracting consumers and generating business income.